1981
DOI: 10.1007/bf02813790
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies on protein plugs obtained by endoscopic retrograde catheterization of the papilla

Abstract: In order to elucidate mechanisms of protein plug formation, histochemical studies were performed on aggregates and protein plugs present in pancreatic juice. Pancreatic juice was obtained from three control subjects and five patients with chronic pancreatitis through endoscopic retrograde catheterization of the papilla. Specimens for staining were prepared in two ways: (1) fixed with 10 per cent formaldehyde, embedded in paraffin and sectioned, and (2) placed on slide glass and fixed with isopropylalcohol. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
1
5
1
1
Order By: Relevance
“…These findings are consistent with the structures identified as containing GP2 in our study. Furthermore, intraductal plugs observed in histological sections from patients with chronic pancreatitis are morphologically and histochemically similar to precipitates found in pancreatic juice collected by endoscopic cannulation of the pancreatic duct from these types of patients (8,18). This implies that in the setting ofchronic pancreatitis the aggregates we have described are intraductal plugs rather than nonspecific precipitates.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…These findings are consistent with the structures identified as containing GP2 in our study. Furthermore, intraductal plugs observed in histological sections from patients with chronic pancreatitis are morphologically and histochemically similar to precipitates found in pancreatic juice collected by endoscopic cannulation of the pancreatic duct from these types of patients (8,18). This implies that in the setting ofchronic pancreatitis the aggregates we have described are intraductal plugs rather than nonspecific precipitates.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that the protein precipitates found in pancreatic juice collected by endoscopic cannulation of the pancreatic duct are similar to intraductal plugs seen in histological sections from patients with chronic pancreatitis. This is based on morphological appearance as well as histochemical findings (8,18). Since it is difficult to obtain surgical specimens that contain intraductal plugs, endoscopic cannulation of the pancreatic duct has made it possible to obtain pancreatic plugs floating within the juice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations